Redox properties of grape wine skin extracts from the Šumadija region: An electron paramagnetic resonance study - Nakarada Đura J.; Marković Srđan Z.; Popović Milan D.; Dimitrijević Milena S.; Rakić Aleksandra A.; Mojović Miloš D. (Srpsko lekarsko drustvo, 2021)
Introduction: Comprising of a unique combination of bioactive polyphenol compounds, grapes are shown to have a beneficial effect on the skin as well as the whole body. They exhibit high antioxidative and antiradical activity through mechanisms of heavy metals chelation, scavenging reactive oxygen species, inhibiting lipid peroxidation, and preserving the integrity of the cell membranes. In the winemaking industry, after crushing and pressing, grape pomace (stems, seeds, pulp, and skin) is removed as a by-product. This valuable source of bioactive compounds is often treated as animal food, compost, raw material in the brewery, but unfortunately mostly disposed of as unusable waste. Aim: The aim of this study was to compare redox properties of absolute EtOH, 50% EtOH, and H2 O grape wine skin extracts in a way of scavenging DPPH radicals, showing that biowaste obtained from grape wineskins could be used as an immense source of bioactive compounds with high antiradical activity. Material and Methods: Electron Paramagnetic Resonance (EPR) spectroscopy was used to detect the activity of grape skin extracts toward DPPH radicals and UHPLC-DAD MS/MS analysis to separate, identify and quantify their active components. Results: The results show that Cabernet Sauvignon and Pinot Blanc grape skin extracts have unexpectedly large potential to remove DPPH radicals from the system. Having in mind the concentration of redox-active components obtained by UHPLC-DAD MS/MS analysis and presented EPR results, there is strong evidence that primarily quercetin 3-O-glucoside, as well as kaempferol 3-O-glucoside, isorhamnetin 3-O-glucoside, kaempferol 7-O-glucoside supplemented with catechin and rutin are responsible for the antioxidative capacity of extracts. Conclusions: This study demonstrates that extracts obtained from grape skins, initially intended as biowaste, exhibit high antiradical activity. The largest quantity of the most redox-active components could be found in 50% EtOH extracts, which we propose to be the starting material for making potent redox-active cosmetic products and dietary supplements.